Motivational factors in the activities and assignments in the teaching-learning process of Intermediate Intensive English level I taught at the Foreign Languages Department of the University of El Salvador - Cruz Arévalo, Edson Josué
The research was developed at the Foreign Languages Department of the University of El Salvador concerning to the topic Motivational factors in the activities and assignments in the teaching learning process of Intermediate Intensive English level I taught at the Foreign Languages Department of the University of El Salvador. This research had as a main objective to research to what extent motivational factors applied by teachers from the Foreign Languages Department induce students´ interest and efforts through the activities and assignments in order to reach a better and effective learning of Intermediate Intensive English level I. The research was carried out by three undergraduate students from Bachelor of arts in English, emphasis in teaching at the Foreign Languages Department of the University of El Salvador. The field to research was the University of El Salvador, School of Arts and Social Sciences, the Foreign Languages Department. The population taken into account involved teachers and students from all the courses of Intermediate Intensive English Level I and it was conducted during the second semester of the year 2012. From the total population of students taking the Intermediate Intensive English Level I courses, an 80% was taken and about the teachers’ population the sample was all of the teachers in charge of those courses. To obtain the necessary information for carrying out the research, the data collection techniques used were surveys and observations making use of questionnaires and checklists. After collecting the information, it was organized, summarized, analyzed and finally reported.